MODEL-MODEL KINERJA KEUANGAN DI DUNIA - Yeni Rokhilawati (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2018)
Financial performance is crucial for the company, it's useful to know the financial position of a company. By knowing the position of finance can help management to take a decision. A decision is very important in running a company. This research aims at; 1. Expose the results of research about the company's financial performance with a variety of variables and approach. 2. Analyze, mengkomparasi and evaluate in depth the financial performance measurement model on enterprise. The method used is by looking for the journal as much as the number and choose a suitable article for juran suggested. The results obtained showed a lot of models used in financial performance as PVB, ROA, ROE, NPM, TOBIN-Q. The conclusion that can be drawn from this article is an awful lot of models used in the measurement of financial performance, but this article must be examined even more so that it could be enhanced again